Physical and social environment as predictors of job satisfaction for seafarers: An empirical study of the shipping industry in Indonesia - Kundori, Kundori; Fauziningrum, Endah; Sukrisno, Sukrisno (Annals of Human Resource Management Research, 2025)
Purpose: This study investigates the impact of physical and social work environments on job satisfaction among seafarers in Indonesian shipping companies, addressing a critical gap in maritime human resource literature. Given the long periods of isolation and high-stress conditions faced by seafarers, understanding workplace dynamics is essential for improving crew retention and operational efficiency. Methodology: A quantitative explanatory survey was conducted with 350 seafarers across different ranks in deck and engine departments of Indonesian-flagged vessels. Stratified random sampling considered variations in work experience, vessel type, and operational route. Data were analyzed using descriptive and inferential statistics with SPSS 26, enabling examination of multiple relationships while controlling for confounding variables. Results: Findings show that both physical (working conditions, safety equipment, living quarters) and social environments (team cohesion, supervisor support, communication) positively influence job satisfaction. Social factors exerted 42% greater influence than physical conditions. Additionally, seafarers with over five years of experience reported 28% higher satisfaction. Open-ended responses underscored the importance of fair conflict resolution and recognition systems. Conclusions: While adequate physical conditions remain essential, investments in the social environment particularly leadership training and communication systems produce stronger effects on satisfaction, challenging industry practices that emphasize physical over social improvements. Limitations: Results are limited to Indonesian seafarers and specific shipping segments, suggesting the need for cross-national and longitudinal studies. Contribution: The study offers evidence-based insights for crew management and advances theoretical understanding of job satisfaction in isolated work environments, with a replicable methodological framework for other maritime contexts.